Assessment of novel oral anticoagulant use within a community teaching hospital - Sultan Alghadeer; Lori Hornsby (Elsevier, 2017)
Background: Novel oral anticoagulants (NOACs) are considered to be at least as effective and safe as warfarin with several advantages such as predictable pharmacokinetics, allowing for standardized dosing without monitoring, a lack of food interactions and fewer drug interactions; however, their misuse could potentially result in patient harm. Objective: To evaluate the appropriate use of the NOACs within a community teaching hospital. Setting: A community teaching hospital in the United States. Method: A retrospective chart review of patients that were prescribed dabigatran, rivaroxaban, or apixaban at our institution from October 2012 through November 2014 was conducted. Main outcome measure: The primary objective was to determine the percentage of patients that were appropriately prescribed NOACs. Secondary objectives were to determine the number of patients who were inappropriately transitioned from warfarin or parenteral anticoagulants to a NOAC or vice versa, the number of incidents when a NOAC was held or discontinued inappropriately before a procedure and the number of bleeding or thrombotic events while taking a NOAC. Results: Of the 113 patients receiving therapy with an NOAC, appropriate prescribing was observed in 79.7%. Dabigatran, rivaroxaban, and apixaban were appropriately prescribed in 73.8%, 88.3%, and 85.8% of patients respectively. Lack of renal dose-adjustment in patients with reduced renal function was the most common reason for inappropriate use (8.8%). Ten out of 38 patients (26%) were inappropriately transitioned from/to other anticoagulants. Two out of six patients underwent a procedure without holding NOACs as recommended prior to surgery. Of all patients receiving NOACs, a total of 3 bleeding incidents were observed, one with each NOAC. Conclusion: The NOACs were appropriately prescribed for the majority of patients within our institution. Future efforts however should focus on ensuring appropriate dose adjustments for renal impairment, procedures for transitioning between NOACs and parenteral anticoagulants, and adequate withholding times for NOACs prior to surgery in order to optimize the management of NOACs usage within our institution.